Influence of composition and density of slags on their strength and filtration parameters (Academic journal Industrial Machine Building Civil Engineering, 2022)
The results of complex studies of the physical and mechanical properties of metallurgical slags are presented. The parameters of non-granular (MSNG) and granular (MSG) varieties of metallurgical slags were comprehensively analyzed. It was established that the differences in the technologies of their production determine the difference in the values of both the granulometric composition and the indicators of physical, strength and filtration characteristics. The direct dependence of strength and filtration indicators on the type of slags, in particular, mainly on the degree of their compaction and to a lesser extent on their moisture content, was revealed. It has been proven that an increase in density from loose to extremely dense causes an increase in the specific adhesion three times in non-granulated slags and two times in granulated slags.
Keywords: granulated and non-granular metallurgical slags; granulometric composition; physical indicators; shear test; strength characteristics; filtering parameters